EXPERIENCE OF COMMUNICATION IN LAND ACQUISITION OF WEST SUMATRA TOLL ROAD DEVELOPMENT PROJECT - Chatra, Emeraldy; Havifi, Ilham; Tifany, Nazlia (Jurnal Ranah Komunikasi, 2024)
The West Sumatra toll road project that connects the city of Padang with Pekanbaru is not running smoothly. The project, which commenced construction in 2020, is experiencing serious problems in land acquisition because it will eliminate productive lands and settlements. People whose lands are intended to be used as toll road bodies refuse for various reasons, including the amount of compensation that is considered not commensurate with their losses. This research is focus about communication between the Government as the party responsible for land acquisition and the community. The research was conducted inductively with a phenomenological approach. The analysis begins by gathering the experience of community communication with the Government in land acquisition and project work. The experience is reduced to three phenomenological reductions: epoche, eidetic, and transcendental. The results of this study are 1) communication between government agencies responsible for land acquisition and the community is at the lowest level, 2) government agencies reduce community resistance due to low compensation even though on the community side the problem is much more complex because it involves the sustainability of economic activities based on agriculture, the obligation to maintain heritage and cultural identity.